Cycling plan. Toward a cycling friendly community. - (:unkn) unknown (My University, 2012)
The Cycling Plan sets out the City s vision for the expansion of cycling as a safe and convenient transportation choice for Surrey residents and visitors. The Plan builds on the 2008 Transportation Strategic Plan (TSP) that identified the importance of cycling in achieving broader transportation and City objectives in the areas of safety, health, accessibility, sustainability, environmental protection, and developing a successful Surrey economy. The development of a new Cycling Plan was identified as an important step to progress the strategic objectives identified in the TSP into deliverable actions with clearer direction and more focus on active and sustainable transportation modes. Consultation played a key role in the Cycling Plan, through online survey, Public Open House, and meetings and feedback from internal and external stakeholders. The need for a comprehensive approach to cover all aspects of cycling was also reflected in the comments received from the public. (City of Surrey)
Keywords: Individualverkehr; Fahrrad; Verkehrsplanung; Fahrradförderung; Radverkehrsförderung; Radverkehrsplanung; Fahrradinfrastruktur; Radverkehrsstrategie; Fahrradfreundliche Kommune